Design, fabrication and performance analysis of a cost-effective photovoltaic interface seawater desalination hybrid system for co-production of electricity and potable water. (15th April 2023) - Lv, Song; Ren, Juwen; Zhang, Qilong; Zhang, Bolong; Lai, Yin; Yang, Jiahao; Chang, Zhihao; Zhan, Zhipeng
Highlights: Photovoltaic interface desalination hybrid system is designed and tested. The influence of different factors on the photovoltaic interface seawater desalination hybrid system is studied. The performance of the system is concluded by comparing the experiment with the model. It achieves an evaporation efficiency of 61.09% and an electrical efficiency of 11.2% under one-sun illumination. Abstract: The combination of photovoltaic and desalination technology has attracted more and more attention because it can produce water and electricity at the same time. However, the traditional photovoltaic desalination cogeneration system has complex structure, large floor area and high investment cost, which is difficult to be applied on a small scale, especially in the fields of uninhabited islands and reefs that are inaccessible and lack investment value. In this work, we designed a new photovoltaic interface desalination coupling system, which has efficient water and electricity production. By changing the fiber structure of carbonized paper and improving the absorption rate, and optimizing the coupling structure of photovoltaic cells and interface materials, the high heat generated by photovoltaic power generation can be carried away to promote power generation and clean water generation. The practical application of the system was also tested, and the experimental results show that the evaporation efficiency of the coupled system can reach 61.09 % at a solar radiation intensity of 1000 W m −2 . The corresponding evaporation rate is 0.94 kg m -2 h −1 . Meanwhile, the electrical efficiency can reach 11.2 %, which is 1.8 % higher than the electrical efficiency of individual PV modules. In addition, the effects of solar irradiance, ambient humidity, cell absorption rate and thermal conductivity on the evaporation efficiency and electrical efficiency of the system were studied by simulation and experiment. The performance of the PV interface solar desalination system is compared in terms of the first law of thermodynamics and external energy. Finally, the economics and the analysis of the device are performed, the cost of interface evaporation material is $1.05 m −2 . Due to the low cost of raw materials, simple material preparation, high evaporation efficiency, and high electrical efficiency, the system offers the possibility of large-scale application of evaporation at the PV interface.